Are we there yet? the family series - Blyton, Enid (Egmont UK Limited, 2016)
Mike, Belinda and Ann love the Summer holidays - whether they're exploring idyllic Sea-gull Cove, bundled in all together into the family caravan, sailing down a narrow canal in a cosy houseboat or sailing the high seas on a glamorous ocean liner, they know they'll always be in for an adventure. And there's always time for their tea!.